Energy, exergy and thermo-economics analyses of hybrid solar, steam turbine and biomass gasification system for hydrogen production by polymer membrane electrolyzer - Kairat Kuterbekov; Asset Kabyshev; Kenzhebatyr Bekmyrza; Marzhan Kubenova (International Journal of Thermofluids, 2024)
This study presents an evaluation of the energy exergy and thermo-economics of a hybrid power generation system that simultaneously produces power, heat, and hydrogen using solar and biomass energy. The system employs a polymer membrane electrolyzer for hydrogen production, with heat exchangers utilized to attain the desired water temperature instead of conventional heaters. The steam turbine section is heated using exhaust gas from the combustion chamber and heated water from the condenser. Simulation of the system's thermodynamic, exergy, and exergy-economic analyses was conducted using the ESS tool. Analytical assessments were performed based on the provided data. The system achieves a power output of 25 MW, marking the highest level for solar-based systems. The results showed that the cost of the solar section, which constitutes around 68 % of the overall cost, rises with the number of mirrors. The exergy destruction rate of the entire system decreases from 25.71 MW to 24.95 MW. The total cost of operating the system increases by 175.5 dollars per hour at the highest temperature and decreases by 173 dollars per hour at the lowest temperature. The power consumption of electrolyzers directly affects the overall cost of the system, with a range of 0.05 to 0.07 MW resulting in total cost changes of 1.52 USD per hour. The transition to the work requiring the most energy by the electrolyzer causes a loss of 0.27 MW of exergy.